Formation of PS through radiative association - Almeida, Amaury A. de; Andreazza, Carmen M. [UNESP]; Borin, Antonio Carlos (Springer, 2020)
Quantum chemical calculations within the multireference configuration interaction with single and double excitation level of theory are presented and used to obtain the rate coefficient for the radiative association of phosphorus and sulfur atoms to form phosphorus monosulfide (PS). The contribution of the 1(2)Sigma(+) state to spontaneous radiative association of the P(S-4) and S((3) P) atoms is more significant for forming PS. The computed rate constant can be represented over the 300-450 K temperature range by the form k(T) = 2.07 x 10(-22)(T/300)(6.21)exp(-371/T) cm(3) s(-1) and over the 450-14,000 K temperature range by the relation k(T) = 3.68 x 10(-18)(T/300)(0.337)exp(-3603/T) cm(3) s(-1), where T is in K.
Keywords: P plus S reaction; PS radical; Thermal rate constant